Identification of Secondary Metabolites Compounds and Antibacterial Activities on The Extract of Soursop Leaf - Dian Riana Ningsih; Zusfahair Zusfahair; Dwi Kartika (Molekul, 2016)
Treatment of bacterial infectious diseases using semi-synthetic antibiotics can lead to resistance, so as to overcome it necessary to search for natural ingredients from plant extracts that has potential as an antibacterial, one of which is the leaf extract of soursop (Annona muricata L.). This study aims to determine the antibacterial activity of soursop leaf against E. coli and identify groups most active chemical compounds from the extracts. Soursop leaves extracted by maceration using n-hexane, chloroform and methanol. The extracts were tested for antibacterial activity using the diffusion method. Extract with the highest activity determined the minimum inhibitory concentrations grow (MIC) and tested the content of secondary metabolites with phytochemical test, subsequently identified using IR spectrophotometer. Soursop leaves with extraction solvent n-hexane, chloroform and methanol to produce n-hexane extract (E1), the chloroform extract (E2), and the methanol extract (E3) with a yield respectively 0.82%; 5.21%; 8.2% and produce antibacterial activity with consecutive inhibition zone of 3.52 mm; 8.34 mm; 3.00 mm. MIC of soursop leaf chloroform extract of the E. coli bacteria that is at a concentration of 1 ppm with inhibition zone of 3.23 mm. Based on the test results phytochemical soursop leaf chloroform extract showed the presence of compounds alkaloids, steroids, saponins and tannins. IR spectrophotometer identification results showed that the chloroform extract of the leaves of the soursop has functional groups OH, aliphatic C-H, C = O, C = C aromatic, CH3, C-O ether and C-H outside the field.